List Jana Pawła II (pragmatyka, struktura, język) - Biniewicz, Jerzy (Stylistyka, 2021)
The experience of time passing , perceived both individually and as a group, being a psychological fact and contributing to complex cultural relations, determines historical knowledge (the interpretation of historical processes and definition of facts). We should remember, when we talk about the interpretation of time, understood as the assessment of historical facts, allowing for the integration of a given society around an idea, around va- lues constituting their cohesion and, to a considerable extent, determining its relations with the outer world, that it is always a product of social discourse, grinding views, a se- arch for such a vision of the futurę with which at least the groups most important to a community’s functioning would identify.The letter of John Paul II addressed to the nations of Poland and Ukrainę, in which the question of evaluating the tragic events in Volyn during World War II was brought up, is the subject of this analysis. The article attempts to answer the question (taking into consi- deration the complexity of the process shaping mutual neighbourly relations) how the Pope endeavours to attain his objective, which is to encourage Poles and Ukrainians to re- concile and to reject the past for the sake of tasks facing united Europę.The Pope’s letter is undoubtedly a speech realized with the use of lexical and stylistic means typical for religious language. At the same time, the analysis shows that certain elements of the letter are typical for the language of politics.The Pope’s text in the world of freedom and pluralism, where numerous political sub- jects make contact with society by means of varied language, escaping explicit assessment, is marked by an expressive, easily recognizable description of reality and ans- wers a common need (the Pope feels responsible for the word, and builds a speaker-reci- pient relationship in order for the reader to become the subject capable of creating the world), thus he is appreciated and noticeable in the world of mass culture.